Is there anything good about conspiracy beliefs? Belief in COVID-19 conspiracy theories is associated with benefits to well-being - Javier A. Granados Samayoa; Courtney A. Moore; Benjamin C. Ruisch; Jesse T. Ladanyi; Russell H. Fazio (PLoS ONE, 2025)
Recent theorizing suggests that people gravitate toward conspiracy theories during difficult times because such beliefs promise to alleviate threats to psychological motives. Surprisingly, however, previous research has largely failed to find beneficial intrapersonal effects of endorsing an event conspiracy theory for outcomes like well-being. The current research provides correlational evidence for a link between well-being and an event conspiracy belief by teasing apart this relation from (1) the influence of experiencing turmoil that nudges people toward believing the event conspiracy theory in the first place and (2) conspiracist ideation—the general tendency to engage in conspiratorial thinking. Across two studies we find that, when statistically accounting for the degree of economic turmoil recently experienced and conspiracist ideation, greater belief in COVID-19 conspiracy theories concurrently predicts less stress and longitudinally predicts greater contentment. However, the relation between COVID-19 conspiracy belief and contentment diminishes in size over time. These findings suggest that despite their numerous negative consequences, event conspiracy beliefs are associated with at least temporary intrapersonal benefits.